2009
DOI: 10.1073/pnas.0911061107
|View full text |Cite
|
Sign up to set email alerts
|

Strict coupling between CFTR’s catalytic cycle and gating of its Cl ion pore revealed by distributions of open channel burst durations

Abstract: CFTR, the ABC protein defective in cystic fibrosis, functions as an anion channel. Once phosphorylated by protein kinase A, a CFTR channel is opened and closed by events at its two cytosolic nucleotide binding domains (NBDs). Formation of a head-to-tail NBD1/NBD2 heterodimer, by ATP binding in two interfacial composite sites between conserved Walker A and B motifs of one NBD and the ABC-specific signature sequence of the other, has been proposed to trigger channel opening. ATP hydrolysis at the only catalytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
221
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(250 citation statements)
references
References 37 publications
15
221
3
Order By: Relevance
“…By scrutinizing their single-channel data, they were able to discern two conductance levels and an uneven distributions of transitions between these two open channel levels, indicating a violation of microscopic reversibility and hence a necessity of an input of free energy-in this case, from ATP hydrolysis (Gunderson and Kopito 1995). This idea of an infusion of free energy in driving (Csanády et al 2010). These investigators showed a paucity of shortlived events that results in an unusual double exponential distributions with a negative component, indicative of a violation of microscopic reversibility.…”
Section: Future Perspectives Regarding Atp-dependent Channel Gatingmentioning
confidence: 99%
“…By scrutinizing their single-channel data, they were able to discern two conductance levels and an uneven distributions of transitions between these two open channel levels, indicating a violation of microscopic reversibility and hence a necessity of an input of free energy-in this case, from ATP hydrolysis (Gunderson and Kopito 1995). This idea of an infusion of free energy in driving (Csanády et al 2010). These investigators showed a paucity of shortlived events that results in an unusual double exponential distributions with a negative component, indicative of a violation of microscopic reversibility.…”
Section: Future Perspectives Regarding Atp-dependent Channel Gatingmentioning
confidence: 99%
“…Extrapolating this result suggests that there may be fundamental thermodynamic bounds on statistical inference. The trade-off between accuracy and energy is general and may be relevant for other signal transduction systems, such as gene regulation [30], light-activated proteins [31] or ligand-gated ion channels [32]. We note that following the tradition of Berg and Purcell, in this paper we only considered estimating a concentration after a long time T .…”
Section: Figmentioning
confidence: 99%
“…1A) for CFTR gating offers a unique mechanism for prolonging the open time of WT-CFTR besides delaying hydrolysis and/or NBD dimer separation implicated in other gating models (25,26). As shown in Fig.…”
mentioning
confidence: 99%
“…Notably, there are brief closings buried within each opening burst known as flickers. However, because these flickering closings were traditionally considered ATP-independent events (12,(26)(27)(28), a computer program had been developed by Csanady et al (29) to isolate the ATP-dependent opening bursts for single-channel kinetic analysis.…”
mentioning
confidence: 99%